2023
DOI: 10.52225/narra.v3i1.142
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Zingiber officinale to reduce inflammation markers and the length of stay of patients with community-acquired pneumonia: An open-label clinical trial

Abstract: Examination of the interleukin 6 (IL-6) and procalcitonin levels, and neutrophil-lymphocyte ratio (NLR) might could help to diagnosis and predict the duration of therapy and prognosis of pneumonia cases. Zingiber officinale var rubrum could be used as an adjunct therapy in infectious diseases as it has anti-inflammatory activity. The aim of study was to assess the effect of Z. officinale on levels of IL-6 dan procalcitonin, NLR, and the length of hospitalization of patients with community-acquired pneumonia (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…An integrated examination of the gene expression data revealed that the anti-inflammatory and immunomodulatory effects of the formulation were comparable to those of hydrocortisone. Z. officinale at 300 mg daily was found to be beneficial in lowering various serum markers of the inflammation process, such as procalcitonin and eutrophillymphocyte ratio in individuals with community-acquired pneumonia ( Reviono et al, 2023 ).…”
Section: Immunomodulating Effects Of Zingiber Speciesmentioning
confidence: 99%
“…An integrated examination of the gene expression data revealed that the anti-inflammatory and immunomodulatory effects of the formulation were comparable to those of hydrocortisone. Z. officinale at 300 mg daily was found to be beneficial in lowering various serum markers of the inflammation process, such as procalcitonin and eutrophillymphocyte ratio in individuals with community-acquired pneumonia ( Reviono et al, 2023 ).…”
Section: Immunomodulating Effects Of Zingiber Speciesmentioning
confidence: 99%